The politeness of criticism speech acts in Japanese and Minangkabau films - Nuria Haristiani; Amelya Septiana; Nor Fariza Mohd. Nor; Nagata Ryota (Indonesian Journal of Applied Linguistics, 2023)
Criticism tends to be a face-threatening speech act that can endanger social relationships if not managed using appropriate strategies, especially in the intercultural context. This study aims to compare and contrast the politeness of criticism speech acts used in Japanese and Minangkabau languages as depicted in film series. The data on criticism speech acts in this study were collected from eleven Japanese film series with a total duration of 538 minutes and eight Minangkabau films with a total duration of 535 minutes. The collected data were formed into a set of data cards, classified based on the criticism speech acts strategies by Nguyen (2005), and analyzed based on Brown and Levinson’s (1987) politeness theory. The data classification in Japanese and Minangkabau was validated through the expert judgment process. The findings indicated that the Japanese and Minangkabau languages employed the same set of criticism speech act strategies but have different tendencies. In Japanese, speakers tend to use indirect strategies as their main criticism speech act strategy by ‘asking/presupposing,’ ‘correction,’ and ‘advice for change.’ Meanwhile, in Minangkabau, speakers tend to use direct strategies by using ‘negative evaluation,’ ‘expression of contradiction,’ and ‘disagreement’ strategies. Regarding the politeness strategy, off-record politeness strategies are more dominantly used among Japanese speakers. In contrast, Minangkabau speakers use bald on-record politeness strategies in criticism speech acts, reflecting their communication culture.  The findings of this study provide a deeper understanding of criticism speech act and politeness strategies. The study is expected to contribute to the area of research on intercultural communication and Sociolinguistics.